A Strategy for Conservation of the Habitat of North-western Population of Indian Elephants - Singh, K. N. (Indian Forester, 2002)
The North-Western Himalayan population of the Indian elephant , Elephss maximus , used to be distributed contigually from the River Yamuna to the River Sharda in the past. This population was studied in the last decade of the twentieth century. The past migration patterns of elephants were compared with current movements in this region. The present day migration of elephants is localized and seems chiefly influenced by fodder and water requirements. The causes behind the fragmentation of elephant habitat mainly river valley projects and major construction works taken up after independence in the wake of development drive have been discussed in detail. The viability and ways means of restoring the possible corridors are discussed and a strategy for the long-term conservation of this population is suggested.